Impact of Antioxidant on Altered Quantity of Testicular Leydig Cell During Anti Cancerous Therapy an Experimental Study - Aisha Abdul Haq, Dureshawar Rehman, Sadia Iqbal, Uzma Hameed, Aisha Hassan Brohi, Amna Mughal (Pakistan Journal of Medical & Health Sciences, 2023)
Statement of Problem: Patients undergoing chemotherapy has been struggling long with side effects on tissues which were not targeted for therapy. Chemotherapeutic agents Doxorubicin (DOX) used in this study induced testicular damage, had been a major concern of oncologists for decades. Studies so far has more focus on the adverse impact of drug on germ cells and very few observed its effect on Leydig cell secreting testosterone. To date few studies are available that have used antioxidant therapy like vitamin C to assuage the oxidative damage induced by DOX on supporting cell like Leydig. Objectives: To demonstrate the altered numbers of Leydig cells produced by DOX in testes of mice and designed to study the changes in quantity of Leydig cells in DOX affected interstitial cells with co-administration of antioxidant ascorbic acid. Research Design: An experimental study to determine the effect of dox on testicular leydig cells and to assess the ameliorating effects of vitamin c on it. Duration of Study: This study was conducted from June 2022 to February 2023 Place of Study: Research was conducted at Dow university of health sciences (DUHS) Karachi at institute of basic medical sciences with collaboration of its animal house and Dow Diagnostic Research and Reference Lab DUHS. Sampling technique: The samples were chosen randomly. In this experiment drugs used include doxorubicin hydrochloride, vitamin c and normal saline on 6th, 8th and 10th day of the study. Methodology: Male mice of five weeks old were segregated into 3 groups. Group- A mice were treated with normal saline, DOX alone was given to group- B animals and DOX + Vitamin C to group- C. At the end of experimental study, testes of sacrificed animals were preserved in Bouin’s fluid and later processing, staining etc. were performed. Results and Statistical Analysis: By using SPSSS version 16, statistical analysis was done, using ANOVA test to evaluate the significance of parameter among different groups studied. Widening of interstitium with significant Leydig hyperplasia (P < 0.00) as compared to controls were seen in group B However co-administration of Vitamin C with DOX significantly decrease was observed in comparison to Group A. Practical Implications: The practical implications of this study for the community are that cancer patients undergoing chemotherapy can potentially benefit from co-administration of vitamin C to reduce the adverse effects on testicular tissue, which may help preserve fertility and hormone production. Improving the quality of life for cancer patients by providing an accessible and potentially effective way to manage chemotherapy-induced side effects. Conclusion: This study suggested that the antioxidant Vitamin C has a role in ameliorating the effects produced by DOX on testis by showing change in altered quantity of leydig cell. Keywords: Doxorubicin, Vitamin C, Mice, Antioxidant, Leydig cells